Body of Knowledge: a practice as research case study on the capacity for dance-theatre to promote wellbeing. Issue 1 (4th March 2014) - Bicknell, Jemma
Abstract : Purpose: – The purpose of this paper is to explore the wellbeing benefits and challenges that arise in dance-theatre performance making with older people. It also addresses the notion of taking artistic risks when making community art. Design/methodology/approach: – This study draws on current research into older people's participatory performance and the impact it has on wellbeing, in relation to a practice as research dance-theatre project: Body of Knowledge in 2012. The analysis draws on primary experiential and secondary data to describe the possible physical, mental, social and emotional benefits of taking part in performance projects, as well as identifying the challenges and criticisms related to this kind of work. Findings: – The physical and mental impacts of participating in dance activity are well documented, but there are also valuable social and emotional effects which are hard to quantify, yet just as valuable. Evidence collected from other projects along with my own research, suggests that along with health benefits, the shared endeavour of taking part in a performance project can help an older person to build confidence, social networks, a sense of purpose and refresh or learn new skills. By encouraging older performance groups to show their work to audiences of mixed ages, it is also possible to challenge ageist perceptions. Originality/value: – This paper draws together current research on the physical, mental, social and emotional value of participatory dance-theatre performance work, in relation to practical findings from a specific project.